Online Learning Vs. Classroom Instruction Of Efl: The Case Of Second Year Licence Students At Kasdi Merbah University-Ouargla (مجلة الواحات للبحوث والدراسات, 2025)
the present paper deals with the comparison between online and classroom instruction of EFL. It raises the problem of whether distance learning can replace the role of the teacher in the traditional classroom. The study aims at bridging the gap between these two contexts of learning via fusing online instruction with face-to-face learning. The experimental type of research was adopted with the quantitative approach where the researcher presented lectures of written expression in both teaching contexts to 2nd year licence students at the University of Ouargla. Also, a questionnaire was administered to 100 students of the same level. The results reveal that online instruction is useful but cannot replace the role of the teacher.Keywords:online learning, face-to-face instruction, EFL, EFL learner, EFL teacher.